Incorporating logic of indigeneity in safeguarding indigenous knowledge of medicinal plants in Malaysia: Case study of the Bidayuh in the district of Serian, Sarawak / Jasmine Anak Edmund Andrew - Edmund Andrew, Jasmine (Institute of Graduate Studies, UiTM, 2016)
In recent years there has been a remarkable revision of the negative perceptions on knowledge traditionally held and practiced by indigenous peoples. A particular aspect of traditional knowledge that has been attracting much attention is indigenous people’s knowledge and uses of medicinal plants. This indigenous knowledge has attracted particular attention for the economic potential it brings from new drug development, as leads provided by indigenous use constitute an important cost-savings factor in research and development. However, knowledge of medicinal plants among indigenous communities is facing the threat of erosion due to rippling forces of globalization and modernization. Studies among the country’s indigenous communities have indicated that Malaysia is equally affected by this phenomenon. The impending loss of this valuable resource has stimulated policy intervention for affirmative action both at the international and national levels aimed at preserving, reinforcing, recording or adapting indigenous knowledge on medicinal plants, primarily through documentation and recording of medicinal plants specie and their uses in traditional treatments…